Case Reports: The Use of Sector Fresnel Prism for Increased Peripheral Visual Field Awareness for Patients with End-Stage Retinitis Pigmentosa and Glaucoma. - Chea, Christine; Marinoff, Rebecca (Optometry & Visual Performance, 2015)
Background: Peripheral field loss from conditions such as retinitis pigmentosa and glaucoma can cause significant disabilities by limiting activities of daily living. Severe peripheral field loss causes mobility difficulties with activities such as identifying and adapting to obstacles in the environment. It can also cause emotional strain and impair quality of life. Because this visual field loss is often slow and progressive, patients may be unaware of these functional implications. In addition to orientation and mobility training, sector Fresnel prism therapy is a complementary visual field awareness technique to help the patients obtain information from the missing field. Case Reports: Two cases are presented with the characteristic functional impairments of severe overall visual field constriction. The first case involves a 58-year-old male with advanced retinitis pigmentosa. The second case is of a 52-yearold male with advanced primary open-angle glaucoma. Conclusion: The use of sector Fresnel prism to improve mobility and spatial awareness has long been a clinically accepted tool for rehabilitating patients with overall constricted peripheral visual fields. The prism reduces the degree of eye movement needed to detect peripheral objects in the environment. With in-office training and mobility training, sector Fresnel prism can be successful in helping the patients increase their peripheral awareness of objects, improve their navigational ability, and improve their quality of life.